Women And Work Choices In The Tourism Sector: A Form Of Women Empowerment - A.A.K AYUNINGSASI; Amrita Nugraheni SARASWATY; M.D. SAIENTISNA (Journal of Tourism Economics and Policy, 2023)
The covid-19 pandemic profoundly influenced the Balinese economy and tourism industry, particularly in Canggu's growing economy. The general purpose of this research is to discover how Canggu women's career options have changed since the rapid development of tourism in recent years, as the effect of tourism downfall during and after the COVID-19 epidemic. The research objective is to analyze the internal and external elements that impact women's decision to enter the workforce. This study adopted a qualitative descriptive analysis based on the research purpose. Female Canggu Village Youth Organization members were explicitly chosen as informants for this study. The interview process findings and researchers' involvement in the field revealed that women's decision-making in Canggu Village was influenced by internal factors, such as education level and personality traits, and external factors, such as cultural customs and the influence of those closest to them. Despite the economic slowdown caused by the COVID-19 pandemic, women in Canggu Village are mainly confident that tourism will become the leading industry driving the Canggu Village economy. The findings of this study are likely to assist local governments, academics working on women's empowerment, gender equality, and sustainable tourist development, as well as other communities working to achieve sustainable development.